MANAGEMENT OF EXPERIENCE ACTIVITIES FOR PRESCHOOLERS IN THE CONTEXT OF REFORMING THE PRESCHOO EDUCATION PROGRAM - Nguyen Thi Manh Tien; Tran Thi Huong (Tạp chí Khoa học, 2024)
Administration of experiential activities for preschoolers is one of the important contents of private preschool management in the context of reforming the preschool education program. However, in Vietnam, most of research projects only focus on experiential activities management without focusing on experiential activities administration for preschool children. Basing on the research results, this article presents the scientific theoretical basis for experiential activities and the administration of experiential activities for kindergarten children in preschools, and proposes measures to renew the administration of experiential activities for kindergarten children in private preschools.